(untitled) (Research, Society and Development, 2021)
The article aims to analyze one of the mechanisms of Democratic Management – the School Council, under the perception of this collegiate body. Applies a qualitative methodology with semi-structured interviews to the holders of the School Councils in four Municipal Schools of Elementary Education, using the content analysis of Bardin. Noteworthy are the registration units: participation, strengthening, sharing, conversation, criticism, among others. The simple statistic showed the direct relationship of 1-Council, 2-Participate and 3-Democratic Management, totaling the percentage of 40.41% of frequencies, and the School Board is the collegiate body that must manage the school.